Terpaan Iklan Televisi Dan Sikap Ibu Rumah Tangga Di Pedesaan Terhadap Makanan Olahan Pabrik - Amalia Dianah; Nurmala Katrina Panjaitan; Eko Sri Mulyani (Jurnal Komunikasi Pembangunan, 2016)
TV food advertisements are designed to cultivate positive portrait of the food advertised. Married rural women have dominant role in providing food for family and more possibility to make TV as the main source of information about food. The study aimed to examine the exposure of TV advertisements about industrial processed food on married rural women, the attitude of married rural women towards industrial processed food, and to analyse relationship between the exposure of TV advertisements and the attitude towards industrial processed food. Based on a survey conducted on 104 married rural women with children,who were TV audience and aged 20-60 in Curugbitung Village, Nanggung District, Bogor Regency, it was known that TV food advertisements exposure of respondents were moderate (56%) and high (44%), while their attitude towards industrial processed food were positive (27%) and neutral (73%). A highly significant positive correlation (r = 0.254, p < 0.01) between TV food advertisements and attitude towards industrial processed food on respondents was revealed by Spearman’s rank test. The results implicated that food TVadvertisements were not respondents’ main source of information about food. Analysis of total food TV content and interpersonal information channel of married rural women would be necessary. Keywords : attitude, exposure, processed food, rural women, TV advertisement